Multifunctional magnesium alloy coating with high biocompatibility and preparation method and application thereof
By forming a MAO-SF/nHAp composite coating on the magnesium alloy, the problem of the rapid degradation rate of magnesium alloy in the body is solved, and the high corrosion resistance and biocompatibility of magnesium alloy implants are achieved, thus reducing hydrogen Release and pH increase promote bone tissue regeneration.
Patent Information
- Application Number
- CN202411612332.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The degradation mechanism of magnesium alloys in the body is complex, especially when the pH is low and the corrosion ion concentration in the solution is high, the degradation rate of magnesium alloys is too fast, causing the implant to lose its mechanical properties before achieving its purpose and precipitate during the degradation process. Hydrogen gas causes local tissue alkalization.
Microarc oxidation (MAO) treatment technology and double-sided ultrasonic atomization spraying technology are used to form a composite coating (MAO-SF/nHAp), where the pores and cracks of the MAO layer are used as silk fibroin/nanohydroxyapatite particles (SF) The binding site of the /nHAp) coating forms a lock structure to improve the binding strength and corrosion resistance of the coating.
It significantly improves the corrosion resistance of magnesium alloy, reduces the hydrogen release rate after implantation, slows the rise of pH around the implant, improves biocompatibility and promotes bone tissue regeneration, and reduces the fiber capsule Thickening and inflammatory responses.
Smart Images

Figure CN119465342A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a multifunctional magnesium alloy coating with high biocompatibility and a preparation method and application thereof, belonging to the technical field of implant coatings. Background Art
[0002] At present, magnesium alloys are becoming a potential alternative to permanent metal implant materials such as titanium alloys due to their excellent mechanical strength, elastic modulus close to that of bones, degradability, antibacterial properties, and other characteristics. Compared with steel and titanium, Mg is one of the essential elements in the human body. The magnesium ions released by magnesium-based implants during degradation can be effectively diluted in body fluids and then utilized, and transported to soft tissues or bones throughout the body through blood and other pathways. Excess magnesium ions can also be excreted from the body through human metabolism and are non-toxic to the human body. However, due to the presence of inorganic salts, proteins, glucose and other bio-organic molecules in the body, the degradation mechanism of magnesium alloys in the body is very complex. Especially when the pH is low and the concentration of corrosive ions in the solution is high, magnesium alloys have the problem of excessive degradation rate. This problem causes magnesium alloys to lose their mechanical properties before achieving their purpose when used as implants in the body, and to precipitate hydrogen during the degradation process, causing local tissue alkalization.
[0003] Coating technology is considered to be an effective method to reduce the corrosion rate of magnesium alloys. With the development of coating technology, including the use of natural organic matter (chitosan, silk fibroin, etc.) or inorganic matter (tricalcium phosphate, hydroxyapatite, etc.), corrosion-resistant coatings are synthesized by micro-arc oxidation (MAO) or immersion fluorination (HF) and other methods, but there are still challenges in the preparation of multifunctional, highly biocompatible, high adhesion and corrosion-resistant coatings.
[0004] Among them, silk fibroin (SF), as a natural fibrin, has reliable strength and has been widely used in clinical practice as a degradable suture. SF also has excellent biocompatibility, extremely low immunogenicity, and controllable biodegradability. The surface protein structure of SF after methanol treatment can be transformed from α helix (primary structure) to β sheet (secondary structure), thereby greatly improving its corrosion resistance. These characteristics determine that SF can be used as an excellent biodegradable material in the corrosion protection of alloys. It has been reported that after solidification, micropores will form on the surface of pure SF solution, providing channels for corrosive media. However, these micropores can be significantly smoothed by adding nanohydroxyapatite particles (nHAp), and hydrogen bonds can be formed between the two to form a stable structure. Natural bones are mainly composed of hydroxyapatite (HA), and nHAp also has excellent biological activity and promotes bone regeneration. In addition, the addition of HA to the complex formed by SF also improves the osteogenesis effect. Mixing the two in a certain proportion as a corrosion-resistant, highly biocompatible, and multifunctional coating is a promising strategy.
[0005] Micro-arc oxidation (MAO) is a widely used method to improve the corrosion resistance of magnesium alloys. Through high voltage treatment, a porous barrier layer is formed on the surface of magnesium alloy to resist corrosion. Although the micropores and cracks on the surface increase the effective surface area and enhance the tendency of cell adhesion, they also increase the tendency of corrosive medium adsorption, causing local premature corrosion or pitting corrosion, and causing the coating to fail. Many scholars have tried to minimize or reduce these micropores by adjusting the micro-arc oxidation parameters in their studies. However, in recent years, many scholars believe that these micropores and cracks can also be regarded as an opportunity. For example, the presence of a porous outer layer in the coating can significantly improve the mechanical intercalation effect of the composite coating, thereby improving the coating adhesion. For example, the sample is immersed in a polydopamine (PDA) or 3-aminopropyltriethoxysilane (APTES) solution to obtain rich functional groups, thereby enhancing the chemical bonding, or the surface is plasma cleaned and activated to increase the surface groups. Some of these methods add chemical substances to enhance the bonding of the coating, but some of the newly added chemical substances may be harmful to the human body in terms of degradation in the body, and the degradation mechanism of the interlayer needs to be further clarified. Although plasma activation is an effective way to physically enhance surface adhesion without damage, it has a short shelf life. The effect of this plasma activation will be greatly reduced after a few hours. Unlike many current methods of improving coating adhesion, MAO coating forms an interlocking structure with the external coating through the surface micropore structure to limit the coating from falling off, and has a longer shelf life. However, how to make the external coating enter the micropores to form a strong structure has become a new problem.
[0006] Therefore, developing a multifunctional magnesium alloy coating with high biocompatibility and a preparation method thereof has become a technical problem to be solved urgently in this field. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a multifunctional magnesium alloy coating with high biocompatibility and a preparation method and application thereof.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing a multifunctional magnesium alloy coating with high biocompatibility comprises the following steps:
[0010] (1) Surface treatment of the magnesium alloy substrate;
[0011] (2) using the magnesium alloy substrate after surface treatment obtained in step (1) as an anode and a stainless steel tank as a cathode, performing micro-arc oxidation treatment on the magnesium alloy substrate in an electrolyte to obtain a magnesium alloy substrate after micro-arc oxidation treatment;
[0012] (3) adding hydroxyapatite particles to deionized water, letting it stand and collecting the supernatant; then adding the supernatant to the silk fibroin solution, stirring until fully mixed, filtering, and obtaining a coating solution; using the coating solution to perform double-sided ultrasonic atomization spraying on the magnesium alloy substrate after micro-arc oxidation treatment obtained in step (2);
[0013] (4) Drying the magnesium alloy substrate sprayed in step (3), then soaking it in a methanol solution for 45 to 75 minutes, washing and drying it, and obtaining a multifunctional magnesium alloy coating with high biocompatibility.
[0014] Preferably according to the present invention, in step (1), the magnesium alloy substrate is an AZ31 magnesium alloy sheet with a thickness of 1 mm, a length and a width of 10 mm, and its specific composition is Al 2.5-3.5%, Zn 0.6-1.4%, Mn 0.2-1.0%, Si 0.08%, Fe 0.003%, Cu 0.01%, Ni 0.001%, and Mg balance, where "%" is the mass percentage.
[0015] Preferably, in step (1) of the present invention, the specific method of the surface treatment is: placing the magnesium alloy substrate in anhydrous ethanol and polishing it to 2000 mesh with sandpaper; ultrasonically cleaning it with anhydrous ethanol for 10 minutes and then with acetone solution for 5 minutes to remove organic matter on the surface of the magnesium alloy substrate, and finally air-drying it in a nitrogen environment.
[0016] Preferably according to the present invention, in step (2), the specific components of the electrolyte are: 8-12 g / L NaOH, 4-8 g / L KF, 12-18 g / L Na2SiO3, and 2-5 g / L glycerol.
[0017] Preferably, according to the present invention, in step (2), the parameters of the micro-arc oxidation treatment are: frequency 550-650 kHz, duty cycle 5-10%, current density 1-2 A / square decimeter, and treatment time 8-12 minutes.
[0018] Preferably, according to the present invention, in step (3), the hydroxyapatite particles are nanometer-sized hydroxyapatite particles, and the mass volume ratio of the hydroxyapatite particles to deionized water is (0.4-0.8):10, unit: g / mL.
[0019] Preferably according to the present invention, in step (3), the mass concentration of the silk fibroin solution is 6-7%.
[0020] Preferably, according to the present invention, in step (3), the silk fibroin solution is prepared according to the following method:
[0021] After the silk cocoons are cut into pieces, they are placed in a sodium carbonate solution, boiled to remove the sericin, then washed with deionized water, and dried in an oven overnight to obtain degummed silk; the degummed silk is dissolved in lithium bromide and kept at 55-65°C for 4-6 hours to obtain silk fibroin glue; the silk fibroin glue is injected into a dialysis bag and dialyzed with deionized water for 3 days, with the deionized water replaced every six hours. Finally, the silk fibroin solution is obtained by centrifugation at 9000 rpm for 15 minutes at 4°C.
[0022] Further preferably, the concentration of the sodium carbonate (Na2CO3) solution is 0.015-0.025 mol / L; the concentration of the lithium bromide (LiBr) is 9-9.5 mol / L, and the mass concentration ratio of the degummed silk and lithium bromide is (0.5-1.5):4, unit: g / ml.
[0023] Preferably according to the present invention, in step (3), the volume ratio of the supernatant to the silk fibroin solution is 1:(1-1.1).
[0024] Preferably, according to the present invention, in step (3), the parameters of the ultrasonic atomization spraying are:
[0025] Spraying times: 20 spraying cycles, curing every 10 cycles; nozzle height: 25mm; liquid flow rate: 400μL / min; gas pressure: 0.02Mpa; gas properties: N2; nozzle moving speed: 25mm / s.
[0026] Preferably according to the present invention, in step (4), the concentration of the methanol solution is 80% and the soaking time is 60 minutes.
[0027] A multifunctional magnesium alloy coating with high biocompatibility is prepared according to the method.
[0028] The multifunctional magnesium alloy coating with high biocompatibility is used in the preparation of magnesium alloy implants.
[0029] Where the present invention is not exhaustive, prior art may be used.
[0030] The technical features of the present invention are as follows:
[0031] The present invention first prepares a porous micro-arc oxidation coating (MAO) on an AZ31 magnesium alloy through micro-arc oxidation treatment, and then uses the pores and cracks of the MAO coating as binding sites to provide an effective load for a silk fibroin / nanohydroxyapatite particle (SF / nHAp) coating, so that the MAO coating and the SF / nHAp coating are fully combined to form a composite coating (MAO-SF / nHAp).
[0032] Bonding mechanism of MAO-SF / nHAp: In the traditional micro-arc oxidation process of magnesium alloys, surface pores are often considered to be an unfavorable factor for corrosion protection. This is because some pores will directly pass through the substrate under the coating, causing early contact between the substrate and the corrosive solution to produce early corrosion. In the present invention, the SF / nHAp mixed solution is evenly crushed by ultrasonic spraying technology, and the crushed powder is transported to the surface of the MAO coating by inert gas and then solidified. Due to the good hydrophilicity of the MAO layer, the solution is evenly infiltrated in the MAO micropores to form a synaptic interlocking structure. The denser and deeper the pores of micro-arc oxidation, the deeper the synaptic structure formed. The formed MAO-SF / nHAp coating performs well in the cross-cut tape test and has better bonding strength than the coating manufactured by similar solution drop casting. The firm coating structure also means that the implant is more reliable in clinical applications and reduces the risk of unknown toxicity caused by adding an intermediate adhesion layer.
[0033] Corrosion protection mechanism of MAO-SF / nHAp: Due to the large amount of corrosive ions in human body fluids, magnesium alloys always begin to corrode the moment they come into contact with body fluids. As corrosion progresses, dense hydrogen bubbles will be generated on the surface. As the bubbles increase and merge, they are released into the solution. This process is always accompanied by an increase in pH. Finally, the surface of AZ31 is covered with the generated Mg(OH)2 and phosphate precipitation. For the MAO-SF / nHAp coating, excellent corrosion resistance is shown in in vitro corrosion. The biodegradability and biocompatibility of SF are determined by its special molecular structure. After SF is treated with methanol immersion, the surface protein conformation is converted from α-helix to β-fold, which significantly improves the corrosion resistance and stability of the silk protein layer. After cracks appear on the surface of the MAO-SF / nHAp coating, the corrosive ions contact the MAO layer, and a second round of protection appears. This also shows that MAO not only plays a role in providing bonding force in the coating, but also maintains its inherent corrosion resistance during the corrosion process. In the corrosion protection of magnesium alloys, the essence of the coating is to isolate the contact between the corrosive ions and the alloy substrate by artificial means. In the present invention, it is not only the SFH coating that protects the magnesium alloy, but also the closely fitting tissues and cells formed in the body after implantation, forming a "tissue growth coating" covering the implant in the early stage of implantation. Since the tissue fluid is the main damage to the implant, the closely fitting tissue cleverly reduces the contact between the tissue fluid and the implant interface. It is reported that by constructing a coating that attracts protein adsorption, the initial hydrogen release can be significantly reduced and biocompatibility (cell adhesion, diffusion and growth) can be enhanced by guiding the surface proliferation of cells. It is also found that cell adhesion has a positive effect on improving the corrosion resistance of the implant. The most critical factor for initial cell adhesion is that the initial dissolution rate of the magnesium alloy surface is low enough, which also provides a new starting point for future research, that is: by constructing a high biocompatible coating to improve the corrosion resistance of the magnesium alloy, this coating is the minimum requirement for maintaining the low corrosion rate of the magnesium alloy in the early stage of implantation. The corrosion resistance effect of this novel coating cannot be fully reflected only in the corrosion experiment in vitro, and may even be very different from the in vivo test results. This also means that before designing a corrosion protection strategy for magnesium alloys, more consideration should be given to the anti-corrosion process in the body, so as to design a more practical in-body protection mode for magnesium alloys.
[0034] The beneficial effects of the present invention are:
[0035] 1. The present invention combines micro-arc oxidation treatment technology and double-sided ultrasonic atomization spraying technology for the first time, using the pores and cracks of the MAO coating as binding sites to provide an effective load for the silk fibroin / nanohydroxyapatite particle (SF / nHAp) coating, so that the MAO coating and the SF / nHAp coating are fully combined to prepare a composite coating (MAO-SF / nHAp).
[0036] 2. The coating preparation method provided by the present invention has low cost, high yield, and environmentally friendly materials. Silk fibroin, as the main material of the coating, is derived from silk cocoons, has low cost and high yield. At the same time, the overall technical process is simple and easy to operate, and large-scale industrial production can be realized.
[0037] 3. The multifunctional and highly biocompatible magnesium alloy coating provided by the present invention is the first to combine the MAO coating and the SF / nHAp coating, which effectively improves the defect of rapid degradation of the magnesium alloy when used as an in vivo implant, significantly improves the corrosion resistance of the magnesium alloy, reduces the release rate of hydrogen after implantation, and slows down the increase in pH value around the implant.
[0038] 4. Compared with bare magnesium alloy, the multifunctional and highly biocompatible magnesium alloy coating provided by the present invention significantly improves the biocompatibility of magnesium alloy, improves the ability of magnesium alloy to promote peripheral angiogenesis and bone tissue regeneration, reduces the thickening of the fibrous capsule around the implant, and reduces the inflammatory response of the surrounding tissue after magnesium alloy implantation. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The present invention is a flow chart of the preparation method.
[0040] Figure 2 The scanning electron microscope images of Example 1 and Comparative Examples 1 to 4 are shown;
[0041] In the figure, A is the AZ31 magnesium alloy sheet after grinding and polishing of Comparative Example 3, with a scale of 100 μm; B is the MAO coating of Comparative Example 4, with a scale of 100 μm; C is the MAO coating of Comparative Example 4, with a scale of 1 μm; D is the MAO-SF / nHAp coating of Comparative Example 1, with a scale of 100 μm; E is the MAO-SF / nHAp coating of Example 1, with a scale of 100 μm; F is the MAO-SF / nHAp coating of Comparative Example 2, with a scale of 100 μm; G is an enlarged image of the MAO-SF / nHAp coating of Comparative Example 1; H is an enlarged image of the MAO-SF / nHAp coating of Example 1; I is an enlarged image of the MAO-SF / nHAp coating of Comparative Example 2.
[0042] Figure 3 The corrosion resistance test results of Example 1 and Comparative Examples 3-4 are shown.
[0043] Figure 4 The results are shown in Table 1. The results are shown in Table 1. The results are shown in Table 1.
[0044] Figure 5 3D simulation reconstruction diagram of the implant volume and the volume of hydrogen released after 1, 4 and 7 weeks of simulated implantation in Example 1 and Comparative Example 3.
[0045] Figure 6 The influence of Example 1 and Comparative Examples 3-4 on pH value.
[0046] Figure 7 It is the mass loss of Example 1 and Comparative Examples 3-4 after in vitro immersion.
[0047] Figure 8 In vitro cell compatibility test of Example 1 and Comparative Examples 3-4;
[0048] In the figure, A is cell live and dead staining, B is the cytoskeleton morphology test after 24 hours, C is the cell morphology observation on the material surface after 48 hours, D is the gray value quantitative analysis of Figure A, E is the gray value quantitative analysis of Figure B, F is the CCK-8 cell viability test, and G is the ALP alkaline phosphatase activity test.
[0049] Fig. 9 The results of the angiogenesis test after implantation of Example 1 and Comparative Example 3;
[0050] In the figure, A is the average area of blood vessels around the implant after subcutaneous implantation; B is the average number of blood vessels around the implant after subcutaneous implantation.
[0051] Fig.10 The HE staining results of the surrounding tissues after implantation of Example 1 and Comparative Example 3 are shown.
[0052] Fig.11 The staining results of the surrounding tissue TB after implantation of Example 1 and Comparative Example 3 are shown.
[0053] Fig.12 The results are shown in Table 1. The results are shown in Table 2. The results are shown in Table 3. DETAILED DESCRIPTION
[0054] The present invention is further described in detail below in conjunction with the accompanying drawings and specific examples, but should not be construed as limiting the present invention. The experimental methods and reagents without specific conditions in the examples are all based on conventional conditions in the art.
[0055] The AZ31 magnesium alloy sheet described in the embodiment has a thickness of 1 mm, a length and a width of 10 mm, and its specific composition is Al2.5-3.5%, Zn 0.6-1.4%, Mn 0.2-1.0%, Si 0.08%, Fe 0.003%, Cu 0.01%, Ni0.001%, and Mg balance, where "%" is mass percentage.
[0056] The silk fibroin (SF) solution used in the examples was prepared according to the following method:
[0057] After the silk cocoons are cut into pieces, they are placed in a 0.02mol / LNa2CO3 solution, boiled to remove the sericin, then washed with deionized water, and dried in an oven overnight to obtain degummed silk; the degummed silk is dissolved in 9.3mol / L LiBr, the ratio of degummed silk to LiBr is 1g:4ml, and the solution is kept warm at 60℃ for 5h to obtain silk fibroin glue; the silk fibroin glue is injected into a dialysis bag and dialyzed with deionized water for 3 days, with the deionized water replaced every six hours. Finally, the solution is centrifuged at 9000 rpm for 15min at 4℃ to obtain a silk fibroin (SF) solution with a mass concentration of 6.6%, which is light yellow overall.
[0058] The hydroxyapatite particles used in the examples are nano-hydroxyapatite particles (99%, diameter = 20 nm, McLean).
[0059] The formula of Hank's solution in the embodiment is: NaCl 8.00g / L, KCl 0.40g / L, CaCl2 0.14g / L, NaHCO3 0.35g / L, MgSO4·7H2O 0.10g / L, MgCl2·6H2O 0.1g / L, Na2HPO4·2H2O 0.06g / L, KH2PO4 0.06g / L, d-glucose 1g / L, NaHCO3 0.35g / L, pH 7.5.
[0060] MC3T3-E1 preosteoblast cell line is available from Wuhan Saiweier Biotechnology Co., Ltd.
[0061] Example 1
[0062] like Figure 1 As shown, a method for preparing a multifunctional magnesium alloy coating with high biocompatibility comprises the following steps:
[0063] (1) placing an AZ31 magnesium alloy sheet in anhydrous ethanol and polishing it to 2000 mesh with sandpaper; ultrasonically cleaning it with anhydrous ethanol for 10 minutes and then ultrasonically cleaning it with an acetone solution for 5 minutes to remove organic matter on the surface of the magnesium alloy substrate; finally air-drying it under a nitrogen environment to obtain a magnesium alloy substrate after surface treatment;
[0064] (2) using the magnesium alloy substrate after surface treatment obtained in step (1) as an anode and a stainless steel tank as a cathode, performing micro-arc oxidation treatment on the magnesium alloy substrate in an electrolyte to obtain a magnesium alloy substrate after micro-arc oxidation treatment;
[0065] The specific composition of the electrolyte is: 10g / L NaOH, 6g / L KF, 15g / L Na2SiO3, 4g / L glycerol; the parameters of the micro-arc oxidation treatment are: frequency 600kHz, duty cycle 8%, current density 1.5A per square decimeter, and treatment time 10 minutes;
[0066] (3) adding 0.4 g of nano-hydroxyapatite particles to 10 mL of deionized water, letting it stand for 120 min, and taking the supernatant; then adding the supernatant to the silk fibroin solution, stirring until fully mixed, and passing through a 120-mesh sieve to obtain a coating solution; arranging the magnesium alloy substrates after micro-arc oxidation treatment obtained in step (2) neatly on a stainless steel plate, and using the coating solution to perform double-sided ultrasonic atomization spraying;
[0067] The volume ratio of the supernatant and the silk protein solution is 1:1; the parameters of ultrasonic atomization spraying are: spraying times: 20 cycles of spraying, curing once every 10 cycles; nozzle height: 25 mm; liquid flow rate: 400 μL / min; gas pressure: 0.02 Mpa; gas properties: N2; nozzle moving speed: 25 mm / s;
[0068] (4) drying the sprayed magnesium alloy substrate, then soaking it in an 80% methanol solution for 60 min, washing and drying it, to obtain a magnesium alloy coating (MAO-SF / nHAp) with high biocompatibility;
[0069] The product prepared in this example is recorded as MAO-SF / nHAp group implant (SFH) in subsequent test examples.
[0070] Example 2
[0071] A method for preparing a multifunctional magnesium alloy coating with high biocompatibility comprises the following steps:
[0072] (1) placing an AZ31 magnesium alloy sheet in anhydrous ethanol and polishing it to 2000 mesh with sandpaper; ultrasonically cleaning it with anhydrous ethanol for 10 minutes and then with an acetone solution for 5 minutes to remove organic matter on the surface of the magnesium alloy substrate; finally air-drying it under a nitrogen environment to obtain a magnesium alloy substrate after surface treatment;
[0073] (2) using the magnesium alloy substrate after surface treatment obtained in step (1) as an anode and a stainless steel tank as a cathode, performing micro-arc oxidation treatment on the magnesium alloy substrate in an electrolyte to obtain a magnesium alloy substrate after micro-arc oxidation treatment;
[0074] The specific composition of the electrolyte is: 10g / L NaOH, 6g / L KF, 15g / L Na2SiO3, 4g / L glycerol; the parameters of the micro-arc oxidation treatment are: frequency 500kHz, duty cycle 5%, current density 1A per square decimeter, and treatment time 12 minutes;
[0075] (3) adding 0.8 g of nano-hydroxyapatite particles to 10 mL of deionized water, letting it stand for 120 min, and taking the supernatant; then adding the supernatant to the silk fibroin solution, stirring until fully mixed, and passing through a 120-mesh sieve to obtain a coating solution; arranging the magnesium alloy substrates after micro-arc oxidation treatment obtained in step (2) neatly on a stainless steel plate, and using the coating solution to perform double-sided ultrasonic atomization spraying;
[0076] The volume ratio of the supernatant and the silk protein solution was 1:1; the parameters of the ultrasonic atomization spraying were: spraying times: 20 spraying cycles, curing once every 10 cycles; nozzle height: 30 mm; liquid flow rate: 600 μL / min; gas pressure: 0.06 Mpa; gas properties: N2; nozzle moving speed: 20 mm / s;
[0077] (4) The sprayed magnesium alloy substrate is dried, then immersed in an 80% methanol solution for 60 minutes, cleaned and dried to obtain a magnesium alloy coating with high biocompatibility.
[0078] Example 3
[0079] A method for preparing a multifunctional magnesium alloy coating with high biocompatibility comprises the following steps:
[0080] (1) placing an AZ31 magnesium alloy sheet in anhydrous ethanol and polishing it to 2000 mesh with sandpaper; ultrasonically cleaning it with anhydrous ethanol for 10 minutes and then ultrasonically cleaning it with an acetone solution for 5 minutes to remove organic matter on the surface of the magnesium alloy substrate; finally air-drying it under a nitrogen environment to obtain a magnesium alloy substrate after surface treatment;
[0081] (2) using the magnesium alloy substrate after surface treatment obtained in step (1) as an anode and a stainless steel tank as a cathode, performing micro-arc oxidation treatment on the magnesium alloy substrate in an electrolyte to obtain a magnesium alloy substrate after micro-arc oxidation treatment;
[0082] The specific composition of the electrolyte is: 10g / L NaOH, 6g / L KF, 15g / L Na2SiO3, 4g / L glycerol; the parameters of the micro-arc oxidation treatment are: frequency 650kHz, duty cycle 10%, current density 2A per square decimeter, and treatment time 8 minutes;
[0083] (3) adding 0.8 g of nano-hydroxyapatite particles to 10 mL of deionized water, letting it stand for 120 min, and taking the supernatant; then adding the supernatant to the silk fibroin solution, stirring until fully mixed, and passing through a 120-mesh sieve to obtain a coating solution; arranging the magnesium alloy substrates after micro-arc oxidation treatment obtained in step (2) neatly on a stainless steel plate, and using the coating solution to perform double-sided ultrasonic atomization spraying;
[0084] The volume ratio of the supernatant and the silk protein solution was 1:1; the parameters of the ultrasonic atomization spraying were: spraying times: 20 spraying cycles, curing once every 10 cycles; nozzle height: 35 mm; liquid flow rate: 600 μL / min; gas pressure: 0.08 MPa; gas properties: N2; nozzle moving speed: 15 mm / s;
[0085] (4) The sprayed magnesium alloy substrate is dried, then immersed in an 80% methanol solution for 60 minutes, cleaned and dried to obtain a magnesium alloy coating with high biocompatibility.
[0086] Comparative Example 1
[0087] A method for preparing a multifunctional magnesium alloy coating with high biocompatibility, the specific steps are the same as those in Example 1, except that, in step (3), the parameters of ultrasonic atomization spraying are: number of spraying times: 10 cycles of spraying, curing once every 10 cycles; nozzle height: 25 mm; liquid flow rate: 400 μL / min; gas pressure: 0.02 Mpa; gas properties: N2; nozzle movement speed: 25 mm / s.
[0088] Comparative Example 2
[0089] A method for preparing a multifunctional magnesium alloy coating with high biocompatibility, the specific steps are the same as those in Example 1, except that, in step (3), the parameters of ultrasonic atomization spraying are: number of spraying times: 30 spraying cycles, curing once every 10 cycles; nozzle height: 25 mm; liquid flow rate: 400 μL / min; gas pressure: 0.02 Mpa; gas property: N2; nozzle movement speed: 25 mm / s.
[0090] Comparative Example 3
[0091] A polished AZ31 magnesium alloy sheet is prepared according to the following method:
[0092] The AZ31 magnesium alloy sheet was placed in anhydrous ethanol and polished to 2000 mesh with sandpaper; after ultrasonic cleaning with anhydrous ethanol for 10 minutes, it was ultrasonically cleaned with acetone solution for 5 minutes to remove organic matter on the surface of the magnesium alloy substrate, and finally air-dried in a nitrogen environment to obtain the polished AZ31 magnesium alloy sheet.
[0093] The product prepared in this example is recorded as AZ31 group implant (AZ31) in the subsequent test examples.
[0094] Comparative Example 4
[0095] A porous micro-arc oxidation (MAO) coating is prepared according to the following method:
[0096] (1) placing an AZ31 magnesium alloy sheet in anhydrous ethanol and polishing it to 2000 mesh with sandpaper; ultrasonically cleaning it with anhydrous ethanol for 10 minutes and then with an acetone solution for 5 minutes to remove organic matter on the surface of the magnesium alloy substrate; finally air-drying it under a nitrogen environment to obtain a magnesium alloy substrate after surface treatment;
[0097] (2) Using the surface-treated magnesium alloy substrate obtained in step (1) as an anode and a stainless steel tank as a cathode, the magnesium alloy substrate is subjected to micro-arc oxidation treatment in an electrolyte to obtain a porous micro-arc oxidation coating (MAO).
[0098] The product prepared in this example is recorded as MAO group implant (MAO) in the subsequent test examples.
[0099] Test example
[0100] 1. The multifunctional magnesium alloy coating (MAO-SF / nHAp) with high biocompatibility of Example 1, the multifunctional magnesium alloy coating (MAO-SF / nHAp) with high biocompatibility of Comparative Examples 1-2, the AZ31 implant of Comparative Example 3 and the micro-arc oxidation coating (MAO) of Comparative Example 4 were observed under a scanning electron microscope. The results are as follows: Figure 2 shown.
[0101] Depend on Figure 2 From A to C, it can be seen that the surface of the AZ31 magnesium alloy sheet after grinding and polishing in Comparative Example 3 is smooth with fine grinding marks. After magnification, the surface of the MAO coating in Comparative Example 4 is rough and has evenly distributed tiny pores. These pores are caused by discharge breakdown during micro-arc oxidation. After measurement, the diameter of the pores ranges from about 0.5 to 2.5 μm.
[0102] Depend on Figure 2 It can be seen from D~I that after 10 cycles of spraying, the MAO coating of Comparative Example 1 was only partially covered, which did not meet the requirements. After 30 cycles of spraying, Comparative Example 2 was found to have severe cracking and even peeling, with the maximum crack reaching 70~80μm, which could not meet the requirements of coating integrity. This is because after the third cycle, there were no MAO micropores on the coating surface to provide embedding sites for the SF / nHAp solution. After the last spray drying, the low embedding force on the surface of the SFH30 coating and the thick coating caused cracking. After repeated tests, it was found that only when the spraying was repeated 20 times (SFH), the coating surface was complete and the visible micropores were completely covered. Although a structure similar to a "crater" can be seen on the coating surface, it is still smooth and flat. Therefore, the ultrasonic spraying 20-cycle group is the most effective and compliant coating.
[0103] 2. Corrosion resistance determination
[0104] The MAO-SF / nHAp implants of Example 1, the AZ31 implants of Comparative Example 3, and the MAO implants of Comparative Example 4 were immersed in Hank's solution at 37°C, with the ratio of implant to Hank's solution being 1 cm 2 : 25ml, 10, 20, 30 days of immersion corrosion test, the results are as follows Figure 3 shown.
[0105] Depend on Figure 3 It can be seen that on the 10th day, the surface of the AZ31 implant of Comparative Example 3 showed obvious cracks, and the formation of corrosion products was observed on the surface, but the corrosion products did not completely cover the alloy surface. On the tenth day, the surface of the MAO group implant of Comparative Example 4 showed a tile crack-like morphology, and no microporous structure was seen on the surface. A thin layer of corrosion products could be seen covering the surface, and large pieces of the MAO layer could be seen falling off. However, the implant of the MAO-SF / nHAp group of Example 1 showed no obvious changes, the coating did not crack, and almost no corrosion products were formed on the surface.
[0106] On the 20th day, the corrosion products and cracks of the AZ31 implants of Comparative Example 3 and the MAO group implants of Comparative Example 4 continued to increase, and in the MAO images, hydrogen pores under the MAO layer caused by the corrosion solution passing through the MAO micropores and reacting with the matrix were also visible. However, the implants of the MAO-SF / nHAp group of Example 1 only showed a degradation trend, with a small amount of pitting corrosion products on the surface and very fine cracks.
[0107] On the 30th day, the AZ31 implant of Comparative Example 3 was almost completely covered by corrosion products, and the corrosion products were a three-dimensional porous network structure in the microscopic image. The implants of the MAO group of Comparative Example 4 also showed more corrosion products, and the characteristic surface structure was basically lost, which means that the coating has completely lost its protective properties. On the surface of the implants of the MAO-SF / nHAp group of Example 1, only more pitting corrosion products were observed on the surface than on the 20th day, and tiny cracks appeared.
[0108] 3. Determination of hydrogen release
[0109] The MAO-SF / nHAp implants of Example 1, the AZ31 implants of Comparative Example 3, and the MAO implants of Comparative Example 4 were immersed in Hank's solution at 37°C, with the ratio of implant to Hank's solution being 1 cm 2 : 25ml, one side facing up, invert the funnel and burette on top. Make the solution fill the burette as much as possible, and record the volume of liquid emptied, that is, the volume of hydrogen released, every 6 hours within 24 hours. The result is as follows: Figure 4 shown.
[0110] Depend on Figure 4It can be seen that the release of H2 from the AZ31 implant of Comparative Example 3 increased rapidly within 24 hours, reaching 1.4±0.1 ml / cm 2 The H2 release of the implants in the MAO group of Comparative Example 4 was 0.125±0.025ml / cm 2 The H2 release of the MAO-SF / nHAp implants in Example 1 was only 0.85±0.05 ml / cm 2 This indicates that the rate of hydrogen generation by MAO-SF / nHAp after implantation will be significantly lower than that of the polished AZ31 magnesium alloy sheet and MAO coating.
[0111] Based on the H2 release within 24 hours of the MAO-SF / nHAp implant of Example 1 and the AZ31 implant of Comparative Example 3, the implant volume and the volume of hydrogen released after 1, 4, and 7 weeks of implantation were simulated and a 3D simulation reconstruction diagram was constructed. The results are shown in FIG. Figure 5 shown.
[0112] Depend on Figure 5 It can be seen that the gas volume of AZ31 at 1, 4, and 7 weeks of simulated implantation was 650.58 mm 3 、120.64mm 3 、50.48mm 3 The gas release volume of MAO-SF / nHAp on the contralateral side was 0 mm 3 、57.17mm 3 、119.56mm 3 This indicates that MAO-SF / nHAp hardly underwent corrosion in the first week.
[0113] 4. Impact on pH value
[0114] The MAO-SF / nHAp implants of Example 1, the AZ31 implants of Comparative Example 3, and the MAO implants of Comparative Example 4 were immersed in Hank's solution at 37°C. The initial pH value of the Hank's solution was 7.5, and the ratio of the implant to the Hank's solution was 1 cm 2 : 25ml, record the pH value of the solution every 12 hours for 72 hours, and the results are as follows Figure 6 shown.
[0115] Depend on Figure 6It can be seen that the pH value of the corrosion solution of the AZ31 implant of Comparative Example 3 increased fastest in the early stage, reaching a maximum of 8.58 after 3 days, while the pH value of the corrosion solution of the MAO-SF / nHAp group implant of Example 1 increased slowly, and the maximum pH value after three days was only 7.9. This also shows that the MAO-SF / nHAp composite coating has an excellent improvement effect on preventing the slow release of hydrogen and alkalization after early implantation of magnesium alloy.
[0116] 5. Mass loss value of in vitro immersion test
[0117] The MAO-SF / nHAp implants of Example 1, the AZ31 implants of Comparative Example 3, and the MAO implants of Comparative Example 4 were immersed in Hank's solution at 37°C, with the ratio of implant to Hank's solution being 1 cm 2 : 25ml, the solution was replaced every 48h to ensure the freshness of the corrosion solution. After immersion, the corrosion products were ultrasonically cleaned with a mixed solution of 10g / L AgNO3 and 200g / L CrO3, then dried with deionized water and weighed. The results are as follows Figure 7 shown.
[0118] The calculation formula of mass loss rate (ML) is: ML%=(M0-M1) / M0×100%, where M0 is the mass of the implant before immersion and M1 is the mass of the implant after immersion.
[0119] Depend on Figure 7 It can be seen that after 20 days, the overall mass loss rate of Example 1 and Comparative Examples 3-4 accelerated, which was consistent with the trend of the corrosion degree of their microscopic morphology. After 30 days, the mass loss percentages of Example 1 and Comparative Examples 3-4 were 18.3%, 10.87%, and 6.04%, respectively. The results of the immersion corrosion test showed that the MAO-SF / nHAp group implant of Example 1 had significantly improved corrosion resistance compared with the AZ31 implant of Comparative Example 3 and the MAO group implant of Comparative Example 4, and the MAO-SF / nHAp film was stable during the immersion process without shedding or failure.
[0120] 6. In vitro cell compatibility test
[0121] The MAO-SF / nHAp implants of Example 1 (SFH), the AZ31 implants of Comparative Example 3 (AZ31), and the MAO implants of Comparative Example 4 (MAO) were placed in a 30-well plate at a ratio of 1.25 cm to medium volume. 2 / mL was soaked at 37℃ for 72 hours to obtain the extract. At the same time, α-MEM without any ingredients was used as the control group (Control), and a total of four groups of sample extracts (Control, AZ31, MAO, SFH) were obtained for subsequent cell tests.
[0122] MC3T3-E1 preosteoblasts were cultured in a cell culture medium containing α-minimum essential medium (α-MEM, Gibco, USA) with 10% fetal bovine serum (Gibco, USA) and antibiotics (1%) at 37° C. and 5% CO 2 to the logarithmic phase. Before the cell test, the implants of the MAO-SF / nHAp group of Example 1, the AZ31 implants of Comparative Example 3, and the MAO group implants of Comparative Example 4 were sterilized under ultraviolet light for 1 hour.
[0123] ①、Cell live and dead staining experiment
[0124] MC3T3-E1 preosteoblasts were cultured at 1×10 4 The cells were seeded at a density of 100 cells / well in a 96-well plate and cultured for 1 day. Then, the extracts of the four groups of samples (Control, AZ31, MAO, and SFH) were used to replace the culture medium and culture the MC3T3-E1 preosteoblasts for 1, 4, and 7 days. The cells were washed three times with PBS buffer and then incubated with fluorescent dyes in a 37°C incubator for 15 min. Fluorescence microscope images of the stained cells were taken using a fluorescence microscope (Leica, Germany). The results are shown in Figure 2. Figure 8 As shown in A.
[0125] Figure A was imported into Fiji software for average gray value analysis, and the results of gray value quantitative analysis are shown in Figure D.
[0126] The fluorescent dye was prepared by adding 5 μL Calcein-AM (2 mM) and 15 μL PI solution (1.5 mM) into 5 mL PBS buffer.
[0127] ② Confocal cytoskeleton test experiment
[0128] MC3T3-E1 preosteoblasts were cultured at 1×10 5The cells were seeded at a density of 100 / well in a 96-well plate and cultured for 1 day. Then, the extracts of the four groups of samples (Control, AZ31, MAO, and SFH) were used to replace the culture medium. MC3T3-E1 preosteoblasts were cultured for 24 hours, and the cells were washed once with PBS buffer. 2 ml of 4% paraformaldehyde (Biosharp, China) was added to each well, fixed at room temperature for 30 minutes, washed three times with PBS, and permeabilized with 0.5% Triton X-100. To observe the cytoskeleton and cell spreading, cell actin and cell nuclei were stained with 1:200 diluted FITC-labeled phalloidin (Biosharp, China) and 1:50 diluted DAPI solution for 1 hour and 5 minutes, respectively, incubated at room temperature in the dark, and then washed three times with PBS buffer for 5 minutes each time. The cells were photographed under a laser confocal microscope (Olympus, Japan). The results are shown in Figure 2. Figure 8 As shown in B.
[0129] Figure B was imported into Fiji software for average gray value analysis, and the gray value quantitative analysis results are shown in Figure E.
[0130] ③Direct cell seeding experiment
[0131] The MAO-SF / nHAp implants of Example 1, the AZ31 implants of Comparative Example 3, and the MAO implants of Comparative Example 4 were placed in a 24-well plate, and MC3T3-E1 cells (1×10 4 Cells were inoculated directly on each group of implants in α-MEM medium at 37°C and 5% CO2 for 48 h. Each group of implants was rinsed three times with PBS buffer, then fixed with 2.5% glutaraldehyde solution at room temperature for 1 h, and then dehydrated in gradient ethanol with concentrations of 50, 60, 70, 80, 90, 95 and 100% for 10 min each. Finally, the surface was observed by SEM after freeze drying for 24 h. The results are shown in Figure 2. Figure 8 As shown in C.
[0132] ④. Indirect cell test experiment
[0133] MC3T3-E1 preosteoblasts were cultured at 1×10 4 The cells were inoculated in a 96-well plate at a density of 100 cells / well and cultured for 1 day. The extracts of the four groups of samples (Control, AZ31, MAO, and SFH) were used instead of the culture medium to culture MC3T3-E1 preosteoblasts for 1, 4, and 7 days. Finally, the cell viability was evaluated using the Cell Counting Kit-8 solution (CCK-8, Solarbio, Beijing). The absorbance was measured at a wavelength of 450 nm to obtain the optical density value (OD). The cell viability was calculated based on the OD value. The results are shown in Figure 8 As shown in F.
[0134] The cell viability calculation formula is: Cell viability (%) = ODsample / ODcontrol × 100%.
[0135] ⑤. Alkaline phosphatase activity test
[0136] MC3T3-E1 preosteoblasts were cultured at 1×10 5 The cells were inoculated at a density of 100 / well in a 96-well plate and cultured for 1 day. Then, the extracts of the four groups of samples (Control, AZ31, MAO, and SFH) were used to replace the culture medium and cultured MC3T3-E1 preosteoblasts for 1, 4, and 7 days. The cells were washed twice with PBS buffer and then the total cell lysate was collected with lysis buffer. The alkaline phosphatase (ALP) activity of the cell lysate was measured and calculated at a measurement wavelength of 405 nm. The results are shown in Figure 8 As shown in G.
[0137] The results of ALP activity were normalized according to the control group data, and the calculation formula was: Cell differentiation activity (%) = ALP sample / ALP control × 100%.
[0138] As shown in Figures A to E, on the first day, there was no significant difference in cell growth among the four groups of samples. On the fourth day, due to the low corrosion resistance of AZ31, the solution formed an over-alkaline environment, and the cell density cultured with AZ31 extract was significantly lower than that of the coating sample. This trend became most significant on the seventh day. Due to the excellent corrosion resistance and high biological activity of SF and nHAp, the extract of the coating sample was stable at a level suitable for cell growth. Compared with the cells in the control group (Control) and AZ31 group, the cells cultured with the coating extract had a larger spreading area and a more obvious cytoskeleton, which also means that SFH has better potential to promote cell proliferation and differentiation. At the same time, most of the cells on AZ31 were spherical in shape, and significant cracks appeared on the surface of the material, which also indicated that the cells had died one after another. According to observations, once AZ31 came into contact with the culture medium solution, hydrogen would continue to be produced on the surface, which was very unfavorable for the surface adhesion of cells. In the coating group, the cells spread on the surface in a fusiform or polygonal shape, especially the surface of the MAO-SF / nHAp coating was smooth, but the cells were tightly attached to the coating surface. This also means that the coating group will have higher biocompatibility and ability to promote tissue growth after implantation in the body.
[0139] Depend on Figure 8 F shows that the cell viability of the AZ31 group at three time points was significantly lower than that of the control group and the coating group. This also shows that the culture medium environment created by AZ31 is indeed not conducive to cell growth, which is consistent with the results of live-dead staining ( Figure 8A) is consistent. Compared with the control group, the cell viability of the MAO group decreased slightly at 4 and 7 days, which may be due to the degradation of the MAO coating, but the degree of degradation is lower than that of AZ31. The cell survival rate of the MAO-SF / nHAp group samples was significantly higher than that of the other groups at 1, 4, and 7 days (P<0.001). This also shows that the SFH coating is not only non-cytotoxic, but also can maintain the integrity of the coating within 7 days to resist the occurrence of corrosion. As a promising bone implant, the osteogenic properties of magnesium alloys are of great concern.
[0140] Depend on Figure 8 G It can be seen that compared with the control group, the ALP activity of the three groups of samples has been significantly increased. This is because the release of magnesium ions can significantly increase the activity of alkaline phosphatase by inducing an alkaline environment. In the MAO-SF / nHAp group, due to the excellent osteogenic activity and biocompatibility of SF and nHAp, the ALP activity of the SFH group is more significant than that of other groups. This is because the surface of silk biomaterials not only provides carboxyl (-COOH), hydroxyl (-OH) and other groups as sites for HA nucleation and bonding, but also promotes the growth of HA along the C axis. And the changes in the structure of the second phase silk protein also improve the osteogenic properties of SFH.
[0141] 7. Determination of angiogenesis performance (average area and average number of blood vessels around the implant after subcutaneous implantation / ROI)
[0142] Sprague-Dawley male 8-week-old rats (N=9; 250-300g; Vital River) were used, and the AZ31 implant of Comparative Example 3 and the MAO-SF / nHAp group implant of Example 1 were implanted subcutaneously on both sides of the dorsal spine of the rats, with an interval of more than 1 cm. No more than 3 rats were placed in each cage, and a 12-12-hour light cycle was given, free access to drinking water and standard rodent food. The surgery was first performed by anesthesia with 4% isoflurane, and the hair in the surgical area was removed and cleaned. Then, subcutaneous pockets on both sides of the back were constructed by incision and blunt separation. The AZ31 implant of Comparative Example 3 was implanted on the left side, and the MAO-SF / nHAp group implant of Example 1 (1mm×10mm×10mm) was implanted on the right side, and finally sutured with non-absorbable sutures. After cleaning the back, wait for the rat to recover, and inject penicillin for infection within one week after implantation, and remove the sutures one week later. The animals were killed with carbon dioxide at 1, 4, and 7 weeks after implantation. Micro-CT (Quantum GX2, PerkinElmer, America, 4 min) was used to photograph and observe the implants and surrounding tissues in the rats. The average area and average number of blood vessels around the implants after subcutaneous implantation were calculated. The results are as follows: Fig. 9 shown.
[0143] Depend on Fig. 9It can be seen that the number of new capillaries in the tissue surrounding the implant plays an important role in tissue healing or bone formation. In the 1st, 4th and 7th weeks, the average vascular area of the implant (SFH) of the MAO-SF / nHAp group of Example 1 was higher than that of the AZ31 group of Comparative Example 3. However, in the fourth week, it was found that although the number of blood vessels of the implant (SFH) of the MAO-SF / nHAp group of Example 1 was reduced, the vascular area was higher, and the difference was significant in the fourth week (P<0.05). This also means that compared with the AZ31 group of Comparative Example 3, the maturity of single blood vessels in the tissue surrounding the implant (SFH) of the MAO-SF / nHAp group of Example 1 is higher. These differences all show that the implant (SFH) of the MAO-SF / nHAp group of Example 1 has better biocompatibility than the AZ31 group of Comparative Example 3, its angiogenesis-promoting ability is stronger, the level of surrounding inflammatory response is weaker, and the proliferation of the surrounding fibrous capsule wall is slower.
[0144] 8. HE staining, TB staining and determination of mast cell numbers around implants
[0145] After the implant was removed, the tissue block was immersed in 4% paraformaldehyde for fixation, dehydrated with ethanol step by step, and then embedded in paraffin. The tissue was sliced in the middle part (thickness 5μm), dewaxed with xylene, and then stained with hematoxylin and eosin (HE) and toluidine blue (TB). A high-definition pathological slice panoramic scanning and image analysis system (Olympus VS120, Japan) was used to shoot under a 40× objective lens. Six consecutive equidistant areas were taken on the superficial and deep sides of the implant as the region of interest (ROI = 500×500μm), and the images were imported into the OlyVIAV4.1 software to measure the number and area of blood vessels around the implant, the number of mast cells, and to mark and analyze inflammatory cells. The results are shown in the figure. Figures 10-11 shown.
[0146] Depend on Figures 10-11 It can be seen that at one week, obvious inflammatory cell aggregation can be seen in the tissues around the implants of the AZ31 group of Comparative Example 3, including a large number of neutrophil and lymphocyte infiltrations, which is related to the early violent reaction of magnesium alloy. The intensity of inflammation will affect the later repair of the tissues around the biomaterial. Compared with the implants of the AZ31 group of Comparative Example 3, the tissues around the implants of the MAO-SF / nHAp group (SFH) of Example 1 performed well, and the new fiber capsule wall was significantly thinner than that of AZ31, and there was almost no inflammatory reaction. And it can also be intuitively seen that the thickness of the fiber capsule around the implants (SFH) of the MAO-SF / nHAp group of Example 1 is significantly lower.
[0147] Depend on Fig.12It can be seen that in the statistics of mast cell numbers, the average number of mast cells in the SFH group was always lower than that in the AZ31 group, and the difference was significant in the first week (P<0.05).
Claims
1. A method for preparing a multifunctional magnesium alloy coating with high biocompatibility, characterized in that: The steps include: (1) Surface treatment of the magnesium alloy substrate; (2) using the magnesium alloy substrate after surface treatment obtained in step (1) as an anode and a stainless steel tank as a cathode, performing micro-arc oxidation treatment on the magnesium alloy substrate in an electrolyte to obtain a magnesium alloy substrate after micro-arc oxidation treatment; (3) adding hydroxyapatite particles to deionized water, allowing the water to stand and collecting the supernatant; then adding the supernatant to the silk fibroin solution, stirring until fully mixed, and filtering to obtain a coating solution; Using the coating solution to perform double-sided ultrasonic atomization spray coating on the magnesium alloy substrate after micro-arc oxidation treatment obtained in step (2); (4) Drying the magnesium alloy substrate sprayed in step (3), then soaking it in a methanol solution for 45 to 75 minutes, washing and drying it, and obtaining a multifunctional magnesium alloy coating with high biocompatibility.
2. The preparation method according to claim 1, characterized in that In step (1), the magnesium alloy substrate is an AZ31 magnesium alloy sheet with a thickness of 1 mm, a length and a width of 10 mm, and a specific composition of Al 2.5-3.5%, Zn 0.6-1.4%, Mn 0.2-1.0%, Si 0.08%, Fe 0.003%, Cu 0.01%, Ni 0.001%, and Mg balance, where "%" is mass percentage; The specific method of the surface treatment is: placing the magnesium alloy substrate in anhydrous ethanol and polishing it to 2000 mesh with sandpaper; using anhydrous ethanol to ultrasonically clean for 10 minutes and then using acetone solution to ultrasonically clean for 5 minutes to remove organic matter on the surface of the magnesium alloy substrate, and finally air-drying it under a nitrogen environment.
3. The preparation method according to claim 1, characterized in that: In step (2), the specific components of the electrolyte are: 8-12 g / L NaOH, 4-8 g / L KF, 12-18 g / L Na2SiO3, and 2-5 g / L glycerol; The parameters of the micro-arc oxidation treatment are: frequency 550-650 kHz, duty cycle 5-10%, current density 1-2 A / square decimeter, and treatment time 8-12 minutes.
4. The preparation method according to claim 1, characterized in that: In step (3), the hydroxyapatite particles are nano-scale hydroxyapatite particles, and the mass volume ratio of hydroxyapatite particles to deionized water is (0.4-0.8):10, unit: g / mL.
5. The preparation method according to claim 1, characterized in that: In step (3), the mass concentration of the silk fibroin solution is 6-7%.
6. The preparation method according to claim 1, characterized in that: In step (3), the silk fibroin solution is prepared according to the following method: After the silk cocoons are cut into pieces, they are placed in a sodium carbonate solution, boiled to remove the sericin, then washed with deionized water, and placed in an oven to dry overnight to obtain degummed silk; the degummed silk is dissolved in lithium bromide, and the solution is kept warm at 55-65°C for 4-6 hours to obtain silk fibroin glue; the silk fibroin glue is injected into a dialysis bag, dialyzed with deionized water for 3 days, the deionized water is replaced every six hours, and finally centrifuged at 9000 rpm for 15 minutes at 4°C to obtain a silk fibroin solution; The concentration of the sodium carbonate solution is 0.015-0.025 mol / L; the concentration of the lithium bromide is 9-9.5 mol / L, and the mass concentration ratio of the degummed silk and the lithium bromide is (0.5-1.5):4, unit: g / ml.
7. The preparation method according to claim 1, characterized in that: In step (3), the volume ratio of the supernatant to the silk fibroin solution is 1:(1-1.1); The parameters of the ultrasonic atomization spraying are: Spraying times: 20 spraying cycles, curing every 10 cycles; nozzle height: 25mm; liquid flow rate: 400μL / min; gas pressure: 0.02Mpa; gas properties: N2; nozzle moving speed: 25mm / s.
8. The preparation method according to claim 1, characterized in that: In step (4), the concentration of the methanol solution is 80%, and the soaking time is 60 minutes.
9. A multifunctional magnesium alloy coating with high biocompatibility, characterized in that: It is prepared according to the method according to any one of claims 1 to 8.
10. Use of the multifunctional magnesium alloy coating with high biocompatibility according to claim 9 in the preparation of magnesium alloy implants.
Citation Information
Cited By
Dental filling material of polyphenol modified magnesium-based powder / biphase calcium phosphate composite powder
CN120733119A